A skill profile of the national women`s Australian football league (AFLW) - Black, G. M.; Gabbett, T. J.; Johnston, R. D.; Cole, M. H.; Naughton, G.; Dawson, B. (Science and Medicine in Football, 2019)
Objectives: To investigate the relationship between technical involvements and (1) winning margins, (2) losing margins and (3) ladder position in the national Australian Football League Women`s competition (AFLW). Methods: The first season of AFLW technical data were analysed. All matches (n = 26) were separated into winning and losing subsets and score margins were recorded. To investigate the influence of technical involvements on overall performance, final ladder position was also recorded. Results: Uncontested possessions and the ratio between the number of times the ball was inside the attacking 50-m zone (inside 50s) and goals scored, were identified as the biggest predictors of match outcomes in the AFLW. Larger winning margins were associated with reduced marks "inside 50" and a lower inside 50: goals scored ratio. Kicks and contested marks demonstrated significant relationships with final ladder position, with these involvements decreasing as the ladder position moved closer to eight. Conclusions: Team game plans should promote the importance of finding space and completing a number of passes in the attacking 50-m zone to allow closer shots on goal. Further to this, coaches may need to draft players who are able to "win" marking contests to improve ladder position in the future seasons.